People With Parkinson’s Disease and Freezing of Gait Show Abnormal Low Frequency Activity of Antagonistic Leg Muscles - Breu, Maria-Sophie; Schneider, Marlieke; Klemt, Johannes; Cebi, Idil; Gharabaghi, Alireza; Weiss, Daniel (Frontiers in Human Neuroscience, 2022)
Objective: Freezing of gait is detrimental to patients with idiopathic Parkinson´s disease (PD). Its pathophysiology represents a multilevel failure of motor processing in the cortical, subcortical, and brainstem circuits, ultimately resulting in ineffective motor output of the spinal pattern generator. Electrophysiological studies pointed to abnormalities of oscillatory activity in freezers that covered a broad frequency range including the theta, alpha and beta bands. We explored muscular frequency domain activity with respect to freezing, and used deep brain stimulation to modulate these rhythms thereby evaluating the supraspinal contributions to spinal motor neuron activity. Methods: We analyzed 9 PD freezers and 16 healthy controls. We studied the patients after overnight withdrawal of dopaminergic medication with stimulation off, stimulation of the subthalamic nucleus (STN-DBSonly) or the substantia nigra pars reticulate (SNr-DBSonly), respectively. Patients performed a walking paradigm passing a narrow obstacle. We analyzed the frequency-domain spectra of the tibialis anterior (TA) and gastrocnemius (GA) muscles in ‘regular gait’ and during the ‘freezing’ episodes. Results: In stimulation off, PD freezers showed increased muscle activity of the alpha and lower-beta band compared to HC in both TA and GA. This activity increase was present during straight walking and during the freezes to similar extent. STN- but not SNr-DBS decreased this activity and paralleled the clinical improvement of freezing. Conclusion: We found increased muscle activation of the alpha and lower beta band in PD freezers compared to HC, and this was attenuated with STN-DBS. Future studies may use combined recordings of local field potentials, EEG, and EMG to interrogate the supraspinal circuit mechanisms of the pathological activation pattern of the spinal pattern generator.